![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
解方程:(1)3x2=4x;(2)2(x-3)2=x2-9;(3)x2-12x-4=0(配方法解);(4)5x2-8x+2=0
解方程:(1)3x2=4x;(2)2(x-3)2=x2-9;(3)x2-12x-4=0(配方法解);(4)5x2-8x+2=0....
解方程:(1)3x2=4x;(2)2(x-3)2=x2-9;(3)x2-12x-4=0(配方法解);(4)5x2-8x+2=0.
展开
1个回答
展开全部
(1)3x2-4x=0,
x(3x-4)=0,
∴x1=0,x2=
;
(2)2(x-3)2-(x+3)(x-3)=0,
(x-3)(2x-6-x-3)=0,
(x-3)(x-9)=0,
∴x1=3,x2=9;
(3)x2-12x=4,
x2-12x+36=40,
(x-6)2=40,
x-6=±2
,
∴x1=6+2
,x2=6-2
;
(4)a=5,b=-8,c=2,
△=64-40=24,
x=
,
∴x1=
+
,x2=
-
.
x(3x-4)=0,
∴x1=0,x2=
4 |
3 |
(2)2(x-3)2-(x+3)(x-3)=0,
(x-3)(2x-6-x-3)=0,
(x-3)(x-9)=0,
∴x1=3,x2=9;
(3)x2-12x=4,
x2-12x+36=40,
(x-6)2=40,
x-6=±2
10 |
∴x1=6+2
10 |
10 |
(4)a=5,b=-8,c=2,
△=64-40=24,
x=
8±
| ||
10 |
∴x1=
4 |
5 |
| ||
5 |
4 |
5 |
| ||
5 |
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询